The Use of an Intraoral Scanner for the Fabrication of Maxillary Obturator Prosthesis in a Young Adult With Oronasal Fistula: A Case Report - Sayed Shojaedin Shayegh; Zahra Mohammadi; Mohammad Amin Bafandeh; Mohammad Reza Nazemalroaya (Case Reports in Dentistry, 2025)
Conclusion: Digital impressions offer precise, efficient, and comfortable fabrication of obturator prostheses compared to conventional methods. Despite initial costs, they reduce chair time, enhance accuracy for dental hard tissues, and improve patient experience, particularly for young patients with cleft lip and palate.